Music and literature in German romanticism - Donovan, Siobhán, 1966-; Elliott, Robin, 1956- (Rochester, N.Y. : Camden House, 2004)
The interrelationship between music and literature reached its zenith during the Romantic era, and nowhere was this relationship more pronounced than in Germany. Many representatives of literary and philosophical German Romanticism held music to be the highest and most expressive, quintessentially Romantic art form, able to convey what cannot be expressed in words: the ineffable and metaphysical. The influence was reciprocal, with literature providing a rich source of inspiration for German composers of both instrumental and vocal music, giving rise to a wealth of new forms and styles. The essays in this volume are selected from papers presented at an international, interdisciplinary conference held at University College Dublin in December 2000, and include contributions from Germanists, musicologists, comparatists, and performance artists. This interdisciplinarity makes for informed and complementary approaches and arguments. The essays cover not only the "Romantic" nineteenth century (commencing with the early Romanticism of the Jena circle), but also look ahead to the legacy, reception, and continuation of German Romanticism in the modern and postmodern ages. Alongside new readings of familiar and established writers and composers such as Goethe, Hoffmann, Wagner, and Schubert, a case is made for other figures such as Wackenroder, Novalis, Schlegel, Schumann, Brahms, Liszt, and Berlioz, as well as less-known figures such as Ritter, Schneider, and Termen, and for a reconsideration of questions of categorization. The essays will appeal to readers with a wide variety of academic, musical, and literary interests.--
Iniquitous innocence : the ambiguity of music in the Phantasien über die Kunst (1799) / Richard Littlejohns -- The cosmic-symphonic : Novalis, music, and universal discourse / James Hodkinson -- "Das Hören ist ein Sehen von und durch innen" : Johann Wilhelm Ritter and the aesthetics of music / Thomas Strässle -- Music and non-verbal reason in E.T.A. Hoffmann / Jeanne Riou -- Perceptions of Goethe and Schubert / Lorraine Byrne -- Goethe's Egmont, Beethoven's Egmont / David Hill -- A tale of two Fausts : an examination of reciprocal influence in the responses of Liszt and Wagner to Goethe's Faust / David Larkin -- Musical gypsies and anti-classical aesthetics : the romantic reception of Goethe's Mignon character in Brentano's Die mehrenen Wehmüller und ungarische Nationalgeschichter / Stefanie Bach -- Stages of imagination in music and literature : E.T.A. Hoffmann and Hector Berlioz / Andrea Hübener -- The voice from the hereafter : E.T.A. Hoffmann's ideal of sound and its realization in early twentieth-century electronic music / Werner Keil -- "My song the midnight raven has outwing'd" : Schubert's "Der Wanderer," D. 649 / James Parsons -- The notion of personae in Brahm's "Bitteres zu sagen denkst du" : op. 32, no. 7 : a literary key to musical performance? / Natasha Loges -- Robert Schneider's Schlafes Bruder : a neo-romantic Musikernovelle? / Jürgen Barkhoff.
Selected papers from the interdisciplinary conference "Music and Literature in German Romanticism" held December 8-10, 2000, at the University College Dublin
Includes bibliographical references and index.
Siobhán Donovan is a Lecturer in the Department of German at University College Dublin. Robin Elliott is Jean A. Chalmers Chair in Canadian Music at the University of Toronto.
Print version record.
English.
JSTOR
Keywords: German literature -- 18th century -- History and criticism -- Congresses; German literature -- 19th century -- History and criticism -- Congresses; Music and literature -- Congresses; Romanticism -- Germany -- Congresses; Littérature allemande -- 18e siècle -- Histoire et critique -- Congrès.; Littérature allemande -- 19e siècle -- Histoire et critique -- Congrès.; Musique et littérature -- Congrès.; Romantisme -- Allemagne -- Congrès.; LITERARY CRITICISM -- European -- German; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; German literature; Music and literature; Romanticism; Germany; 1700-1899; German romanticism; Congress; Conference papers and proceedings; Criticism, interpretation, etc; Conference papers and proceedings; Actes de congrès.